Percorsi dell’incertezza verso la tecnoscienza - Giuseppe Tipaldo (Quaderni di Sociologia, 2011)
As a part of a still on-going five-years research conducted on the social impact of the presently under-construction incineration plant in the city of Turin, Italy, the paper has its own background in the scientific domain known as Science-Technology-Society studies (STSs). One of the 320 environmental conflicts at the moment spread across the country, the Turin case is here used as a revelatory case for a critical discussion about uncertainty, risk and the increasingly deep tensions between Science and Society, lay public and expertise. Moreover, a multi-technique approach, including lexical correspondence analysis, is adopted to gather empirical evidence about the hypothesis, eventually verified, that public images of Science, Technology and scientists actually have a significant influence on the attitude towards the plant.